PENGARUH KEMAMPUAN, LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA DOSEN DI UNIVERSITAS BANGKA BELITUNG - Andy Evans Gunady; Yanto Yanto (LPPM STIE PERTIBA Pangkalpinang, 2018)
This study aims to analyze the influence of the work environment and the ability to motivate either simultaneously or partially. Furthermore, to analyze the influence of ability, work environment, the motivation of the Pacific Islands University lecturer performance. The size of the sample set is 95 of the total 123 lecturers University of the Pacific Islands. Instrument research using questionnaires, which are arranged in a scale of 1-5, a score of 1 to a very poor response and a score of 5 for the excellent responses. The method of analysis using path analysis model of trimming (path analysis). Hypothesis testing using the F test (simultaneous) and t-test (partial). The research concludes that there is a significant effect of variable abilities, motivational work environment against either simultaneously or partial, and there is a significant effect of variable abilities, work environment, motivation on the performance of both simultaneously and partial the views of the coefficient of determination of 81.1 percent.